IDENTIFIKASI Pseudomonas aeruginosa PADA PENGGUNA KAWAT GIGI - Viona Syafaattullah; Yusianti Silviani (LPPM Universitas Abdurrab, 2026)
Dental and oral health problems in Indonesia have a prevalence of 57.6%. This condition is related to the activity of microorganisms in the oral cavity, which can develop due to poor oral hygiene. The use of orthodontic appliances such as braces can increase the risk of plaque buildup and changes in the oral microbiota because the appliance components are difficult to clean. One of the bacteria potentially found in these conditions is Pseudomonas aeruginosa, an opportunistic gram-negative bacterium capable of forming biofilms. The purpose of this study was to identify the presence of Pseudomonas aeruginosa in individuals using fixed orthodontic appliances. This study used a descriptive observational design with a cross-sectional approach. Sampling was carried out by swabbing the orthodontic users' braces using a purposive sampling technique. Inclusion criteria were wearing braces for at least 4 weeks, brushing their teeth at least twice a day, and having no cavities. The samples were then cultured on BHI media, followed by cultivation on MacConkey media, Gram staining, and identification using biochemical tests. The results of a study of 12 samples showed the presence of Pseudomonas aeruginosa bacteria in 25% of the samples. Klebsiella pneumoniae was also found in 50% of the samples, while the remaining samples contained bacteria from the Enterobacteriaceae group. These findings indicate that various types of Gram-negative bacteria can colonize the surface of orthodontic appliances in braces users. Based on the results of the study, it can be concluded that Pseudomonas aeruginosa bacteria were found in 25% of braces users.